Evaluation of the Government's Makassar Recover Program in Makassar City - Didin Halim; Herlina Sakawati; Triyani Setiawan; Ahmad Wahidiyat Haedar (Universitas Negeri Makassar, 2022)
This study aims to identify and analyze the Government's Makassar Recover Program in Makassar City, using a qualitative approach. Collecting data using observation techniques, interviews, and documentation. Data obtained from processing results using interactive model analysis including data collection, data condensation, data presentation, and conclusion testing. The results showed that the evaluation of the Makassar Recover program by the Makassar City Government was based on four dimensions including context, input, process, and product, on health immunity, social adaptation, and economic recovery. The context dimension shows that the Makassar Recover program for health immunity and social adaptation is running optimally, but the economic recovery program is showing suboptimal results. The input dimension indicates the availability of human resources and budget. The process dimension shows that the Makassar Recover program is carried out according to standard operating procedures and strict regulations. The product dimension shows that the Makassar Recover program has produced a synergy between the role of the community and the government in overcoming the impact of the Covid-19 virus and social adaptation, but economic recovery has not shown satisfactory results. The determinant factors in this study indicate the existence of strict regulations, resources which include the quality of human resources and budgets, as well as culture in realizing Makassar Recover in Makassar City.